Ascend - Hocking, Amanda (New York : St. Martin's Griffin, 2012)
Duty-bound to marry her friend Tove in order to give the Trylle people their strongest king and queen in history, Wendy, a changeling troll princess, is torn between two other suitors, Finn and Loki.
"New! Bonus story inside"--Cover.
Originally self-published, with slightly different text, as an e-book in 2011.
Keywords: Princesses -- Fiction; Trolls -- Fiction; Changelings -- Fiction; Supernatural -- Fiction; Love -- Fiction